ANALYSIS OF THE QUALITY OF HEALTH SERVICES ON PATIENT SATISFACTION AT THE PUBLIC HEALTH CENTER : A LITERATURE REVIEW - Windarti, Aprilia; Toni Herlambang; Abadi Sanosra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to determine patient satisfaction with the quality of health services at the health center. Method: This article uses the literature review method following the PRISMA guidelines. Data was obtained from the Google Scholar electronic database. The keyword used was "analysis of health service quality on patient satisfaction at the health center" to find relevant articles. The search results found 9,390 articles. Articles that did not meet the inclusion criteria were excluded. A total of 6 articles containing an analysis of health service quality on patient satisfaction at public health centers were selected for analysis in this study. Results: The articles showed that patient satisfaction at health centers is influenced by the dimensions of health service quality. The factors that influence the satisfaction of patients seeking treatment at health centers are tangible, reliability, responsiveness, assurance, and empathy. Novelty: To increase patient satisfaction, health centers need to continue to make improvements by enhancing the quality of health center services.